A sense of coherence and health. Salutogenesis in a societal context: Åland, a special case? - Eriksson, Monica (BMJ Group, 2007)
BACKGROUND: Antonovsky's salutogenic concept of a sense of coherence (SOC) has proved most influential in the way that health is now perceived. AIM: To (1) describe the distribution of SOC among 40–70‐year‐old Ålanders; (2) examine the distribution of depression in Åland, Finland, and its relationship with SOC; and (3) discuss the findings within a salutogenic framework in a societal context. DESIGN: A cross‐sectional study design was adopted. Antonovsky's SOC Questionnaire (13 items) and the Beck Depression Inventory (13 items) were used. In addition, in a separate questionnaire, sociodemographic information about each participant was sought, together with a question specific to this study and designed to measure self‐rated health. SETTING: Åland, an autonomous island province of Finland. RESULTS: The proportion of respondents reporting good health was high (64%). The overall mean (SD) SOC was 70.7 (11.7) points, whereas for farmers and fishermen it was 73.88 (8.8) and 74.33 (9.2) points, respectively. SOC was significantly and strongly related to the self‐rated health score. The higher the SOC, the better was the health of the respondents. Furthermore, the study provided clear evidence of the potential of the SOC concept as a positive mental health indicator. CONCLUSION: The SOC seems to be a health‐promoting resource that supports the development of a positive subjective state of health.